Analysis Pragmatic Competence in Student Interviews With Foreign Tourists in Seminyak, Bali - Ni Luh Desy Suari Dewi; I Gede Neil Prajamukti Wardhana; Yohanes Octovianus L. Awololon (Pusat riset dan Inovasi Nasional, 2025)
In Indonesia and many other EFL contexts, English is often taught in structured classroom settings that rely on scripted dialogues and controlled practice. This limits students’ exposure to spontaneous, real-life communication, reducing their ability to use English naturally and appropriately in authentic situations. This study investigates the pragmatic competence of Indonesian students during English interview interactions with foreign tourists, using Grice’s Cooperative Principle as the theoretical framework. Five video recordings were analyzed, featuring elementary and secondary students conducting unscripted interviews with tourists at Seminyak Beach, Bali. While the students generally demonstrated adequate grammatical control and vocabulary range, the findings reveal recurring challenges in sustaining natural and cooperative conversations. The most frequent violations involved the Maxims of Relation, Quantity, and Manner, with students often failing to respond appropriately to tourist answers, providing minimal elaboration, or speaking in unclear and disorganized ways. The results highlight the need for English language teaching to include explicit instruction in pragmatic skills, such as turn-taking, topic development, and interactional awareness.